2020
DOI: 10.1109/tcsii.2019.2937654
|View full text |Cite
|
Sign up to set email alerts
|

A Harmonic Rejection Strategy for 25% Duty-Cycle IQ-Mixers Using Digital-to-Time Converters

Abstract: Due to the use of wide-band analog front-ends in order to cover the many different frequency bands used in Long Term Evolution (LTE), blocker signals received by the antenna may reach the mixer input. As a consequence, square-wave mixer implementations, as, e.g., the 25% duty-cycle current-driven passive mixer, may lead to the down-conversion of these blocker signals by their harmonic response. This contribution describes a harmonic rejection (HR) strategy, which modifies the local oscillator (LO) waveform of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There is a growing research on programmable and reconfigurable mixer-first RF front-ends and partly this is achieved by tunable mixers and filters at the receiver RF front-end [1]- [3]. Most of these mixer-first RF front-ends [4], higher order filtering RF front-ends [5], frequency selective passive front-ends [6] employ RF sampling and they operate at a frequency close to or greater than the input RF frequency(f RF ), requiring high performance frequency synthesizers with stringent phase noise, jitter requirements leading to increased power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing research on programmable and reconfigurable mixer-first RF front-ends and partly this is achieved by tunable mixers and filters at the receiver RF front-end [1]- [3]. Most of these mixer-first RF front-ends [4], higher order filtering RF front-ends [5], frequency selective passive front-ends [6] employ RF sampling and they operate at a frequency close to or greater than the input RF frequency(f RF ), requiring high performance frequency synthesizers with stringent phase noise, jitter requirements leading to increased power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…An HR issue is considered irrelevant for narrowband radio along with the off-chip filtering components. However, recent trends favor the wide-band analog front-end in order to cover vastly different frequency bands and to lower the cost of the RF transceiver, especially in Long Term Evolution (LTE) [7]. Thus, blocker signals may reach the HR mixer where the harmonic alias rejection is usually in the range of 40-50 dBc only [5,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…The present work is intended to exploit the model possibilities, increasing the number of modulation ratios, introducing the concepts of macroperiod and duty cycle to the time modulation, with the objective of enriching the diffraction phenomenon. Furthermore, it has been shown that breaking the temporal symmetry allows the suppression of non-desired harmonics [42]. The scattering parameters are quantitatively evaluated, constituting an additional contribution with respect previous works in the literature.…”
mentioning
confidence: 98%